The art of prevention: COVID-19 vaccine preparedness for the dermatologist - Shauna M Rice, BS; Sarah D Ferree, MD; Natasha Atanaskova Mesinkovska, MD, PhD; Arianne Shadi Kourosh, MD, MPH (Wolters Kluwer, 2021)
As COVID-19 vaccinations begin, dermatologists must be aware of the cutaneous adverse events reported in the clinical trials, including injection site and hypersensitivity reactions, and emerging evidence of dermal filler injection reactions after vaccination. The filler reaction may represent the development of a delayed-type hypersensitivity in the setting of another immunologic trigger (i.e., the vaccine). After conducting a literature review of similar reactions, their pathophysiology, and management, we present a set of timely clinical considerations for counseling, prevention, and management of possible cutaneous sequelae of the COVID-19 vaccine. We encourage documentation of vaccine-related reactions to aid the safety data collection in the Vaccine Adverse Event Reporting System and the American Academy of Dermatology COVID-19 Registry.